(3cJGH ajg MbGFb eG jXgQ bOGe ehdGfG Ld PcQg ef GdgRds - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hPdc HGdJCjjO dbGFe GdReGf eXgQ GdcdeI hGdHjGf Ydi PcQg GdSdGe GdMeO dehdGfG hMOg hTOg SdWGfg HSe Gddg GdQMef GdQMje UaGJ YHOg GdEeGe s
(3BNQgG (B:s
(3hbfG YPGH GdfGQ jYfi GdJNdU ef GdTQjYJjf LejYkG aYdjce eYGTQ GdENhGf GdehMOjf JeJ GdQSGdI HMeO ehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJhMjO hGdedd hGdfMds